2017
DOI: 10.1007/s00270-017-1680-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Conservative Therapy for Symptomatic Isolated Celiac Artery Dissection

Abstract: Conservative treatment can be applied successfully in most patients with symptomatic ICAD. Most cases of symptomatic ICAD resolve spontaneously within 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…[ 1 , 3 , 4 , 6 8 , 13 , 14 ] Previous studies have revealed that SICAD mainly occurs in male patients in their fifth decade of life (male ratio ranging from 82.6% to 100%; age ranging from 40 to 61 years) and abdominal pain being reported as the most common symptoms ranging from 82.6% to 100%. [ 1 , 6 8 , 10 , 15 18 ] Results of the current study revealed that demographic characteristics of SICAD patients were similar to those reported in previous studies. In our series, SICAD was more common in men (90.5%; 19/21), smokers (42.9%; 9/21), and hypertensive subjects (38.1%; 8/23).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…[ 1 , 3 , 4 , 6 8 , 13 , 14 ] Previous studies have revealed that SICAD mainly occurs in male patients in their fifth decade of life (male ratio ranging from 82.6% to 100%; age ranging from 40 to 61 years) and abdominal pain being reported as the most common symptoms ranging from 82.6% to 100%. [ 1 , 6 8 , 10 , 15 18 ] Results of the current study revealed that demographic characteristics of SICAD patients were similar to those reported in previous studies. In our series, SICAD was more common in men (90.5%; 19/21), smokers (42.9%; 9/21), and hypertensive subjects (38.1%; 8/23).…”
Section: Discussionsupporting
confidence: 85%
“…[ 1 , 4 , 6 8 , 10 , 14 23 ] Sixteen (10.9%) of these 147 patients treated by conservative management had treatment failure. [ 1 , 6 , 7 , 15 , 18 20 , 23 ] Therefore, 10.4% (17/164) patients with SICAD needed invasive treatment as their initial treatment, and conservative management failed in 10.9% (16/147) patients. [ 1 , 4 , 6 8 , 10 , 14 23 ] CTA findings for 9 patients among 17 patients who initially underwent invasive treatment were described as follows; aneurysmal dilation (n = 5), [ 7 ] extension of celiac branch (n = 2), [ 23 ] huge aneurysm (n = 1), [ 21 ] and celiac trunk rupture (n = 1), [ 20 ] largely correspond to type IV dissection in morphologic classification of current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Complete resolution of the dissecting aneurysm was defined as disappearance of the dissecting aneurysm on images; partial resolution was defined as < 100% shrinkage of the dissecting aneurysm with residual dissecting aneurysm visible on images. 12 Good stent patency was defined as patency of the stented arteries without any evidence of in stent re-stenosis.…”
Section: Definitionsmentioning
confidence: 99%